2005
DOI: 10.1007/s00066-005-1403-x
|View full text |Cite
|
Sign up to set email alerts
|

Significant Negative Impact of Adjuvant Chemotherapy on Health-Related Quality of Life (HR-QoL) in Women with Breast Cancer Treated by Conserving Surgery and Postoperative 3-D Radiotherapy

Abstract: HR-QoL measurement using EORTC instruments during/after radiotherapy is reliable. Adjuvant chemotherapy significantly lowered HR-QoL versus hormones or radiotherapy alone. Chemotherapy patients did not recover longitudinally (from t1 to t3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…This may be explained by the fact that more women with invasive breast cancer have undergone systemic treatment, which is known to be associated with adverse physical consequences possibly reducing the HRQL significantly. 19 The results in general are in close correspondence with the findings of the study by Rakovitch and colleagues, who conducted a similar study among Canadian patients, although at a different time point after the diagnosis. 4 Like in the present study, these investigators also failed to find significant differences between patients with DCIS and invasive breast cancer concerning risk perceptions and knowledge about the disease.…”
Section: Discussionsupporting
confidence: 89%
“…This may be explained by the fact that more women with invasive breast cancer have undergone systemic treatment, which is known to be associated with adverse physical consequences possibly reducing the HRQL significantly. 19 The results in general are in close correspondence with the findings of the study by Rakovitch and colleagues, who conducted a similar study among Canadian patients, although at a different time point after the diagnosis. 4 Like in the present study, these investigators also failed to find significant differences between patients with DCIS and invasive breast cancer concerning risk perceptions and knowledge about the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Eight studies were graded as high 9, 20, 24, 26–29, 51, 12 as moderate 11, 13, 19, 30–32, 38, 44–46, 48, 49, and seven as low methodological quality 22, 23, 25, 33, 43, 47, 50. The quality scores ranged from six (low) to 14 (high) (mean ± standard deviation 10 ± 2.2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one moderate‐quality study found significantly more memory and concentration problems in BC patients treated with cyclophosphamide/methotrexate/5‐fluorouracil (CMF) compared with lymph node‐negative BC patients (not treated with chemotherapy), four years after treatment 11. One low‐quality study found more SCD in patients treated with radiotherapy in combination with hormone therapy compared to patients treated with only radiotherapy six weeks after ending radiotherapy 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, effective chemotherapy for palliation with a view to health-related quality of life [4] has not been established yet.…”
Section: Discussionmentioning
confidence: 99%